Future teachers and their attitude towards inclusion of people with disabilities. A gender perspective. - Novo-Corti, Isabel; Muñoz-Cantero, Jesús-Miguel; Calvo-Babio, Nuria (Anales de Psicología / Annals of Psychology, 2014)
The inclusion of people with disabilities is a priority in advanced societies. To get it, education is one of the best tools. In this paper, we have studied the support for the inclusion of students with disabilities in the university environment. Our work is related to the theoretical model proposed by the Theory of Planned Behavior and was performed by using data obtained through a survey conducted at the University of A Coruña (Spain) during the 2010-2011 academic year, to 621 students from all degrees in Education Science. The results show the importance of gender as a differentiating factor, revealing a greater involvement of women compared to men, in the stimulus of the inclusion of their university peers suffering disability. The relevance of these results increases if we consider the social impact of this higher involvement of this group (women), that is majority in the primary education, when the formation of attitudes is developed